Repitencia en la Licenciatura en Matemáticas de la UPTC - Velandia Medina, Leidy Johana (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: This study has as its base theme the repetition in higher education students, taking into account that this is a problem that limits the development and progress of students towards their professional promotion, in addition, it is a latent factor for educational desertion. Under these precepts, the present study aims to analyze the relationships established in the repetition of subjects and the main factors that determine it, referring to the students of the Mathematics Degree at the Pedagogical and Technological University of Colombia; For the fulfillment of this purpose, a critical social paradigm, a mixed approach methodology and a type of correlational research are adopted; The analysis is based on primary data from surveys applied to both students and teachers. As a result, it was found that the students participating in the research belong to families of strata one (40%) and two (53%), due to their status as students, many are unemployed and dependent on their families (63%). Referring to the level of repetition of these students, it was found that this phenomenon is present in all semesters, being more frequent in the sixth and seventh semesters; denoting major problems with areas of lines topology, calculus, geometry and logic; Concerning the factors that negatively influence the fulfillment of academic objectives and lead to repetition, according to the students these are economic (39%), followed by learning deficiencies (26%) and academic difficulties (21%). However, the processing and statistical analysis carried out by the author through the chi or Chi-square test (Χ2) (the best known and used for the analysis of qualitative variables) does not show a significant connection between repetition and the factors mentioned by students because all p values were greater than 0.05 or 5%.